High‐Rate and Selective CO2 Electrolysis to Ethylene via Metal–Organic‐Framework‐Augmented CO2 Availability. Issue 51 (16th November 2022) - Nam, Dae‐Hyun; Shekhah, Osama; Ozden, Adnan; McCallum, Christopher; Li, Fengwang; Wang, Xue; Lum, Yanwei; Lee, Taemin; Li, Jun; Wicks, Joshua; Johnston, Andrew; Sinton, David; et al.
Abstract: High‐rate conversion of carbon dioxide (CO2 ) to ethylene (C2 H4 ) in the CO2 reduction reaction (CO2 RR) requires fine control over the phase boundary of the gas diffusion electrode (GDE) to overcome the limit of CO2 solubility in aqueous electrolytes. Here, a metal–organic framework (MOF)‐functionalized GDE design is presented, based on a catalysts:MOFs:hydrophobic substrate materials layered architecture, that leads to high‐rate and selective C2 H4 production in flow cells and membrane electrode assembly (MEA) electrolyzers. It is found that using electroanalysis and operando X‐ray absorption spectroscopy (XAS), MOF‐induced organic layers in GDEs augment the local CO2 concentration near the active sites of the Cu catalysts. MOFs with different CO2 adsorption abilities are used, and the stacking ordering of MOFs in the GDE is varied. While sputtering Cu on poly(tetrafluoroethylene) (PTFE) (Cu/PTFE) exhibits 43% C2 H4 Faradaic efficiency (FE) at a current density of 200 mA cm − 2 in a flow cell, 49% C2 H4 FE at 1 A cm − 2 is achieved on MOF‐augmented GDEs in CO2 RR. MOF‐augmented GDEs are further evaluated in an MEA electrolyzer, achieving a C2 H4 partial current density of 220 mA cm −2 for CO2 RR and 121 mA cm −2 for the carbon monoxide reduction reaction (CORR), representing 2.7‐fold and 15‐fold improvement in C2 H4 production rate, compared to those obtained on bare Cu/PTFE. Abstract : Efficient electrochemical carbon dioxide (CO2 ) conversion into value‐added chemicals requires gas diffusion electrode (GDE)‐based electrolyzers. For high‐rate ethylene (C2 H4 ) production with *CO dimerization, a microenvironment with high CO2 availability near the active sites is essential. Metal–organic‐framework‐induced organic layers in the GDE enable augmentation of the local CO2 concentration and promotion of electrochemical CO2 reduction at high current densities.